Modeling and Simulation of PID Controller-Based Active Suspension System for A Quarter Car Model - Nguyen, Van Trang; Duong, Nguyen Hac Lan (Journal of Technical Education Science, 2022)
The most common automotive suspension systems have been used passive components with fixed damping coefficient and spring constant. They are two separate functions to reach a compromise between drive quality and handling performance. Because of the limit of structures, the passive suspension system could hardly enhance the two features at the same time. In recent years, the active suspension system has been widely used in a vehicle which can overcome the limitations of the passive suspension systems. Since there are many advantages to make the vehicle operate safer and quieter than the passive suspension system. The aim of this study is to develop a linear mathematical model of active and passive suspensions systems for quarter car models subjected to different road profiles using a Proportional Derivative Integral (PID) controller. After modeling and simulation of the suspension system using Matlab/Simulink, this study has been able to determine the parameter of PID controllers of active suspension in many different road surfaces and vehicle speeds to improve driving comfort. Another new point of this study is the Graphical User Interfaces to be a successful design. The users can enter the input parameters for Matlab processing and get the results, which can make system analysis faster and more convenient. The main outcomes of this paper are performed to investigate and compare the response between active and passive suspension systems. Through the analysis of the simulation results, this research has demonstrated the feasibility, reliability, and they can be applied to propose a further improvement of the kinematic and dynamic characteristics of the vehicle active suspension system.